From boardbook to Facebook children's services in an interactive age - Fasick, Adele M (Santa Barbara, Calif. Libraries Unlimited, 2011)
This book presents practical new approaches for extending children's library services beyond the library building, utilizing technology to bring learning to children wherever they may be
Children's services moving into the future -- section i : Changes in children's lives -- section ii: Literacies for the 21st century -- section iii: Buildings for the future -- section iv: Preparing to meet the future
Includes bibliographical references (p. [147]-151) and index
Keywords: Children's libraries -- United States; Interactive multimedia -- United States; Children's libraries -- United States; Interactive multimedia -- United States; Library Science; Electronic books